Large-scale fatigue testing of post-installed shear connectors in partially-composite bridge girders. (October 2019) - Ghiami Azad, Amir Reza; Kreitman, Kerry; Engelhardt, Michael; Helwig, Todd; Williamson, Eric
Abstract: Many older bridges are constructed with structural systems consisting of a non-composite concrete deck over steel girders. A potentially economical method for strengthening these bridges is to develop composite action by attaching the existing concrete deck to the steel beams using post-installed shear connectors comprised of adhesive anchors. Because fatigue is one of the main concerns in designing bridges, investigating the fatigue properties of these post-installed shear connectors is crucial. Although the fatigue life of post-installed shear connectors has been explored through direct-shear tests, the actual fatigue performance of post-installed shear connectors in large-scale beam tests has not been extensively studied and may differ from component tests. The current paper describes the results of large-scale beam experiments on the fatigue performance of post-installed shear connectors. The results of this research indicate that adhesive anchor post-installed shear connectors have much better fatigue performance in beam tests compared to the previously reported fatigue test results based on direct-shear tests. Highlights: The adhesive anchor post-installed shear connector is an excellent candidate for retrofit of non-composite bridges. The adhesive anchor post-installed shear connector exhibits better fatigue behavior than conventional welded shear studs. The adhesive anchor showed better fatigue performance in large-scale beam tests compared to component tests.